2013
DOI: 10.1007/s11481-013-9471-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphate Released from HIV-Infected Macrophages Regulates Glutamatergic Tone and Dendritic Spine Density on Neurons

Abstract: Despite wide spread use of combination antiretroviral therapy (cART) in developed countries, approximately half of HIV-infected patients will develop impairments in cognitive function. Accumulating evidence suggests that neuronal dysfunction can be precipitated by HIV-infection of macrophages by mechanisms that involve alterations in innate and adaptive immune responses. HIV-infection of macrophages is known to increase the release of soluble neurotoxins. However, the composition of products released from infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Our work also concurs with findings from another laboratory demonstrating that P2X receptors mediate increases in neuronal [Ca 2+ ] i and the culling of dendritic spines in rat hippocampal neurons treated with supernatant from HIV infected monocytes (Tovar-y-Romo et al, 2013). Although further work is needed to expand the understanding of the underlying molecular pathways associated with cation-permeable, ligand-gated purinergic receptors, we propose that members of the P2X receptor subfamily may be valuable therapeutic targets for the treatment of neuroAIDS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our work also concurs with findings from another laboratory demonstrating that P2X receptors mediate increases in neuronal [Ca 2+ ] i and the culling of dendritic spines in rat hippocampal neurons treated with supernatant from HIV infected monocytes (Tovar-y-Romo et al, 2013). Although further work is needed to expand the understanding of the underlying molecular pathways associated with cation-permeable, ligand-gated purinergic receptors, we propose that members of the P2X receptor subfamily may be valuable therapeutic targets for the treatment of neuroAIDS.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, P2X receptors may affect AMPA and NMDA receptor levels and function (Gordon et al, 2005; Pankratov et al, 2009; Tai et al, 2010; Baxter et al, 2011), which suggests P2X receptors on neurons and glia may be exerting control over [Ca 2+ ] i through both direct and indirect effects. This concept has also recently been alluded to elsewhere in the context of HIV neuroinflammation (Tovar-y-Romo et al, 2013). …”
Section: Discussionmentioning
confidence: 94%
“…An emerging literature demonstrates the importance of extracellular ATP purinergic signaling in viral infections, specifically, those caused by HIV-1 (21,22,(31)(32)(33). While limited data on other enveloped viruses exist, it is reported that internalization of pseudotyped HIV was not reduced by purinergic inhibitors (12).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is widely accepted that neurodegeneration is one of the principal hallmarks of HAND that occurs without neuronal infection. Brain degeneration and consequently neuronal apoptosis is triggered by signaling of viral products such as Tat and gp120 (Kaul and Lipton 1999; Bansal et al 2000; Gurwell et al 2001; Kaul et al 2001; Hisaka et al 2004; Thomas et al 2009; Merino et al 2011; Zhang et al 2011), cytokines and chemokines (Lee et al 2011; Vazquez-Valls et al 2011; Yan et al 2011; Johansson et al 2013; Lombardelli et al 2013), or by toxins produced from infected macrophages including lysosomal protease cathepsin B(Ciborowski and Gendelman 2006; Tian et al 2008; Turchan-Cholewo et al 2009; Sun et al 2010; Luo et al 2010; Rodriguez-Franco et al 2012; Tovar-Y-Romo et al 2013; Malla et al 2014). Furthermore, studies demonstrated that cocaine can amplify the immune response and cause neuroinflammation (Clark et al 2013) via dysfunction of the BBB (Dhillon et al 2008; Gandhi et al 2010) through alterations of tight junction proteins (Dhillon et al 2007), increased glial activation, and induction of neuroinflammatory pathways (Yao et al 2011; Kousik et al 2012).…”
Section: Introductionmentioning
confidence: 99%